A Micro-ethnographic Study of Big Data-Based Innovation in the Financial Services Sector: Governance, Ethics and Organisational Practices - Arthur, Keren Naa Abeka; Owen, Richard (Journal of business ethics, 2019)
Our study considers the governance, ethics and operational challenges associated with the acquisition, manipulation and commodification of 'big data' in the financial services sector. To the best of our knowledge, there are no published studies describing empirical research undertaken within companies in this sector to understand how they are responding to such challenges: our field-based research is a significant initial contribution in this respect. We describe the results of a microethnographic study undertaken in a small-to-medium-sized company developing disruptive, technology-related platforms and services in the banking and retail sectors based on big data and associated analytics: these are used to derive commercially valuable insights from personal customer data in exchange for cash back and targeted rewards. The company was found to employ a multi-level innovation governance approach, underpinned by an ethical strategy based on a principle of mutual benefit (among stakeholders). Opt-in and informed consent for using data for specific purposes was supported by principles of data minimisation and anonymisation, with unrestricted use of secondary, anonymised and aggregated data to develop insights. Governance, which included contextual data protection legislation, payment-card industry data usage standards and internal corporate controls, presented as bespoke organisational practices relating to data security and privacy. These in total set the governance and ethics frame for big data innovation at the company within which it has had to be both adaptive and responsive under conditions of normative and regulatory uncertainty.